Prosocial priming and bystander effect in an online context - Scaffidi Abbate, Costanza; Misuraca, Raffaella; Vaccaro, Chiara; Roccella, Michele; Vetri, Luigi; Miceli, Silvana (Frontiers in Psychology, 2022)
The present study tested the effect of priming the concept of prosociality on the bystander effect in an online environment. Participants were sent an e-mail requesting a plea for help and randomly assigned to one of four conditions in a 2 (Bystander: 0 vs. 14) × 2 (Priming: present vs. absent) design. The results demonstrated support for the study hypothesis. As expected, the virtual presence of many others significantly reduced e-mail responsiveness except when the request for help is preceded by prosocial priming. Implications of these findings for the literature on the bystander effect and priming are discussed.